2022
DOI: 10.1111/petr.14262
|View full text |Cite
|
Sign up to set email alerts
|

Publication rate and research topics of studies in pediatric kidney transplantation

Abstract: Approximately 1700 children suffering from chronic kidney disease stage 5 in Europe and the United States of America undergo kidney transplantation each year. 1,2 A successful kidney transplantation is considered as the best therapeutic option regarding long-term patient survival and quality of life. 3,4 Outcomes have markedly improved over the last decades, particularly due to the introduction of modern

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…13 Earlier, a study had found significant publication bias in This is consistent with prior work suggesting publication bias in smaller samples of paediatric trials. [14][15][16][17][18][19][20][21] However, there has been no prior research comprehensively assessing the nature and reporting behaviour of paediatric trials in apparent violation of the FDAAA.…”
Section: Introductionmentioning
confidence: 99%
“…13 Earlier, a study had found significant publication bias in This is consistent with prior work suggesting publication bias in smaller samples of paediatric trials. [14][15][16][17][18][19][20][21] However, there has been no prior research comprehensively assessing the nature and reporting behaviour of paediatric trials in apparent violation of the FDAAA.…”
Section: Introductionmentioning
confidence: 99%